The Application of Smart Contracts in Cybersecurity for Threat Detection and Response - Prasetyo, Stefanus Eko; Wijaya, Gautama; ., Kennedi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
Cybersecurity is becoming an increasingly important issue in the digital era due to the rise in threats and attacks on information systems. One innovative technology with great potential to enhance cybersecurity is smart contracts. This article discusses the application of smart contracts in detecting and responding to cybersecurity threats. With their automatic, transparent, and immutable nature, smart contracts can be used to manage threat responses in real-time, improve attack detection efficiency, and minimize the risk of human error. This study also explores use cases such as secure data access management, blockchain-based anomaly detection, and incident response automation. Furthermore, implementation challenges such as scalability, interoperability, and smart contract code vulnerabilities are also addressed to provide a comprehensive overview. Through the integration of smart contracts into cybersecurity, this article concludes that this technology holds great potential to strengthen information systems' resilience against increasingly complex and dynamic threats.